A long, dark shadow : minor-attracted people and their pursuit of dignity - Walker, Allyn, 1987- (University of California Press, 2021)
"Challenging widespread assumptions that persons who are preferentially attracted to minors--often referred to as 'pedophiles'--are necessarily also predators and sex offenders, this book takes readers into the lives of non-offending minor-attracted persons (MAPs). There is little research into non-offending MAPs, a group whose experiences offer valuable insights into the prevention of child abuse. Navigating guilt, shame, and fear, this universally maligned group demonstrates remarkable resilience and commitment to living without offending and to supporting and educating others. Using data from interview-based research, A Long, Dark Shadow offers a crucial account of the lived experiences of this hidden population"--